THE EFFECTIVENESS OF IMPROVING STUDENT MATHEMATICS LITERACY THROUGH THE USE OF THE FACEBOOK APPLICATION - Hari Mansah; Islamiani Safitri (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
This study is informed by the poor level of mathematics literacy among Indonesian students. One strategy to improve mathematics literacy is to leverage innovations in Information and Communication Technology (ICT), which are now undergoing rapid development, as seen by the availability of different types of social media applications. The aim of this study was to investigate the effectiveness of the Facebook application in improving mathematics literacy. This research was conducted in the odd semester of the 2021/2022 academic year at the State Senior High School 1 of DolokSigompulon (SMAN 1 DolokSigompulon), North Padang Lawas Regency. All the students in class XI were included in this study. Students in class XI-Science 1 served as the sample in this study. The descriptive quantitative methodology was adopted in this investigation. Questionnaires and tests are used to collect data. The descriptive analysis technique was included in this study. The results of this research indicate that using the Facebook application to improve students' mathematical literacy is quite effective. As evidenced by the questionnaire instrument's results, using the Facebook application for mathematical literacy is "very good." Similarly, the test instrument for mathematical literacy skills, which utilizes the Facebook application, yields "good" results.